An online home-based exercise program improves autonomic dysfunction in breast cancer survivors - Lavín-Pérez, Ana Myriam; Collado-Mateo, Daniel; Hinojo González, Carmen; Batista, Marco; Mayo, Xián; Ruisánchez Villar, Cristina; Jiménez, Alfonso (Frontiers in Physiology, 2023)
Introduction: Exercise interventions for breast cancer survivors have proved their potential to improve clinical, physical, and psychosocial outcomes. However, limited studies have explored exercise effects on autonomic dysfunction and the measurement of exercise tolerance and progression through daily heart rate variability (HRV).Purpose: To analyze the effects of a 16-wk exercise intervention on the autonomic modulation of breast cancer survivors, as well as to examine the evolution of daily measured HRV and its interaction with exercise sessions in this population.Methods: A total of 29 patients who had undergone chemotherapy and radiotherapy were randomly assigned to the exercise group or to the control group. The exercise intervention was delivered remotely through online meetings and consisted of supervised training resistance and cardiovascular exercise 3 times per week. During the intervention all patients measured their HRV daily obtaining the napierian logarithm of the root mean square of successive differences between normal heartbeats (lnrMSSD) and the napierian logarithm of the standard deviation of the interbeat interval of normal sinus beats (lnSDNN) values at four moments: day 0 (the morning of the training sessions), 24h, 48h and 72h after exercise. This is a provisional file, not the final typeset article Results: The results revealed a significant interaction between group and months during the intervention period for lnrMSSD and lnSDNN (p<0.001). Additionally, there were significant differences in lnSDNN recovery time between months (p<0.05), while differences in lnrMSSD become apparent only 24 hours after exercise (p=0.019). The control group experienced a significant decrease in both variables monthly (p<0.05) while exercise group experienced a significant increment (p<0.05).Conclusions: HRV is daily affected by exercise training sessions in cancer patients. Although results strongly support the role of exercise as a post-chemotherapy and radiotherapy rehabilitation strategy for breast cancer survivors to improve autonomic imbalance, further research is necessary to validate these initial findings.